Seasonal timing in a changing world: the epigenetic link between environment and reproduction across taxa - Viitaniemi, Heidi M; Stevensson, Tyler J; Husby, Arild (Oxford University Press (OUP), 2026)
All plants and animals must time their annual reproduction to seasonal variation in resources to optimize reproductive fitness. Environmental factors such as photoperiod and temperature are well known to influence seasonal timing of reproduction but how organisms incorporate environmental cues to alter physiological responses and initiate reproduction remains poorly characterized at the genetic level. A growing number of studies have found that epigenetic mechanisms, such as noncoding RNA, histone modification, and DNA methylation, can have an important role in modifying transcriptional regulation of traits related to seasonal timing. While epigenetic modifications act differently across taxa, there is consistent evidence for their involvement in the timing of seasonal life-history transitions. Here, we discuss the way in which environmental cues trigger epigenetic modifications and propose several roles for their involvement in the regulation of seasonal phenotypes in plants, invertebrates, and vertebrates.